KEBIJAKAN HUKUM OTONOMI DAERAH DALAM PERSPEKTIF KESEJAHTERAAN SOSIAL PMKS PROVINSI KALIMANTAN TIMUR (REGIONAL AUTONOMY LAW POLICY PERSPECTIVE IN SOCIAL WELFARE PMKS OF EAST KALIMANTAN PROVINCE) - Muhammad Soleh Pulungan (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2018)
Abstract Indonesian independence has reached the age of 72 years (1945-2017), but the national goal of the intellectual life of the nation and realize the welfare of the people can not be realized, so the social gap is still quite high. The objectives of research are; (1). To analyze how the principles of regional autonomy policy in PMKS Social Welfare Implementation. (2). To analyze the concept of the Government to realize the State of Welfare (welfare state) in Indonesia. (3). To analyze local legal policy in implementing Social Welfare in East Kalimantan. Research Methods are normative legal research, which focuses on the object of research on the Regulation of Laws. Research result; The principles of regional autonomy policy in support of social welfare regulation for PMKS, has been regulated in Law no. 11 Year 2009 on Social Welfare jo. PP. No. 39 of 2012 on the Implementation of Social Welfare. But the implementation does not run in accordance with the provisions of the regulations governing it. This is because it is not supported by the legal culture of the community, as well as the empowerment of PMKS that runs slowly, and the number of PMKS is increasing. In order to conduct better social welfare of PMKS, it should be established in East Kalimantan a more specific regulation on PMKS, namely three categories; Poverty, the practice of prostitution and drug abuse. The regulation should focus more on empowerment and protection of PMKS, so that the handling of PMKS can run simultaneously in order to address Social Welfare for all Indonesian people. Keywords: autonomy, welfare, PMKS, legislation, social.